AI as authentic material in second language learning: exploring the role of artificial intelligence in enhancing language acquisition - Robles Cabrera, Camila (My University, 2025)
This report explores the use of ChatGPT and BranchTrack as authentic materials in the Spanish second language classroom, aiming to facilitate the learning process for college students. It analyses how these AI systems promote active engagement and authentic language use and foster learner autonomy. The study involves participants who are learning Spanish as a second language and are currently at an intermediate-mid level according to the ACTFL proficiency guidelines. Findings suggest that AI can promote learner autonomy and create a positive and engaging classroom experience, with students generally open to its use. However, challenges such as reliability and ethical implications must be addressed, as concerns persist about AI replacing teacher-student interaction, emphasizing that AI should serve as a supportive tool rather than a replacement for the teacher.
Keywords: Artificial intelligence; Second language acquisition; BranchTrack; ChatGPT; Spanish; Engagement